Effect of antiresorptive drugs in the alveolar bone healing. A histometric and immunohistochemical study in ovariectomized rats - Ramalho-Ferreira, Gabriel [UNESP]; Faverani, Leonardo Perez [UNESP]; Momesso, Gustavo Antonio Correa [UNESP]; Luvizuto, Eloá Rodrigues [UNESP]; de Oliveira Puttini, Igor [UNESP]; Okamoto, Roberta [UNESP] (Springer Nature, 2017)
Objectives: The aim of this study is to evaluate the alendronate and raloxifene influence in the alveolar healing process of osteoporotic rats. Materials and methods: Sixty-four female rats were divided in four groups: sham rats (SHAM), ovariectomized rats and no medical treatment (OVX NT), ovariectomized rats and submitted to alendronate treatment (OVX ALE), and ovariectomized and submitted to raloxifene treatment (OVX RAL). The histomorphometrical and immunohistochemical analysis was performed. The quantitative data were analyzed through Kruskal-Wallis and Dunn tests (α = 0.05). Results: In the longest period, SHAM and OVX RAL groups showed the better bone formation responses (P < 0.05). The worst bone formation response was observed in the group OVX NT. OVX RAL group showed the better response at 42 days. OVX ALE group showed a favorable response at 14 days, in comparison with OVX RAL group, but a reduced response at 42 days. It was possible to observe a mature bone in SHAM group at 14 days and an immature bone in the OVX NT group. An intermediate quality bone was observed in the groups OVX ALE and OVX RAL. Conclusion: Alendronate and raloxifene treatment improved the alveolar healing process in osteoporotic rats, but not enough to achieve the histometrical and protein expression values that were observed in the SHAM group. Clinical relevance: Alendronate is largely used as a potent antiresorptive agent. Otherwise, considering the undesirable effects in relation to the alveolar healing, other antiosteoporosis medications should be studied. Raloxifene seems to be a good candidate once its action mechanism involves the activation of osteoblasts.
Keywords: Alendronate; Osteocalcin; Osteoprotegerin; Raloxifene; RANKL